2015
DOI: 10.1159/000433604
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Complication of Ventriculoperitoneal Shunt with Bladder Perforation and Extrusion through the Urethra in a Newborn: Case Report and Review of the Literature

Abstract: Ventriculoperitoneal shunt (VPS) surgery is a standard procedure for the management of hydrocephalus. Bladder perforation is an extremely rare complication of VPS surgery. Herein, we present for the first time an acute complication of VPS with bladder perforation and extrusion through the urethra in a newborn. We also reviewed the complication of VPS with bladder perforation as reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In our case, the patient did not present signs or symptoms of infection initially, but the culture of the CSF was positive. For this reason, we recommend the culture of both, the CSF and the removed system, as well as other authors do [8]. Some authors recommend two treatment strategies [2].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our case, the patient did not present signs or symptoms of infection initially, but the culture of the CSF was positive. For this reason, we recommend the culture of both, the CSF and the removed system, as well as other authors do [8]. Some authors recommend two treatment strategies [2].…”
Section: Discussionmentioning
confidence: 96%
“…Prasad et al [7] suggested that this perforation is caused by a series of events such as catheter fixation, penetration and eventual perforation of the bladder wall, with subsequent exteriorization through the urethra [7,8]. De Aquino et al [9] argue that the presence of inflammatory phenomena can facilitate the adhesion of the catheter to a viscera, which together with the increase of intra-abdominal pressure and peristaltic movements can produce the erosion and perforation [8,9]. This could explain what occurred in our case since days before we had detected the presence of free intraperitoneal fluid and fat with inflammatory characteristics around the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Organ perforation by distal catheter is relatively unusual. [67] Bowel perforation was present in 0.1%–0.7% of cases in which colon was the most involved organ,[8] and the most common site of extrusion is anus (68.9%), followed by scrotum (22%), umbilicus (6.9%), and vagina (3.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[123] Common complications include malfunction, infection, and overdrainage. [4] Migration of distal part of VP shunt into the adjacent organs including bowel tract, thoracic cavity, heart, scrotum, umbilicus, abdominal wall, and urinary bladder is reported.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous externalization of VPSs is rare. Reports exist of spontaneous or provoked migration of VPS through the umbilicus, mouth, vagina, ureter and penis, to the colon, the scrotum, the anus and extrusion through the spinal area [1][2][3][4][5] .…”
mentioning
confidence: 99%